In vivo waveguide elastography: Effects of neurodegeneration in patients with amyotrophic lateral sclerosis. Issue 6 (17th December 2013) - Romano, Anthony; Guo, Jing; Prokscha, Torben; Meyer, Thomas; Hirsch, Sebastian; Braun, Jürgen; Sack, Ingolf; Scheel, Michael
<x xml:space="preserve">Abstract</x> Purpose Waveguide elastography (WGE) combines magnetic resonance elastography (MRE), diffusion tensor imaging (DTI), and anisotropic inversions for a determination of the elastic properties of white matter. Previously, the method evaluated the anisotropic elastic properties of the corticospinal tracts (CSTs) of healthy volunteers. Here, the sensitivity of WGE is tested for the detection of pathologic changes in a cohort of patients with Amyotrophic Lateral Sclerosis (ALS). Methods MRE and DTI were performed in 14 patients with ALS and 14 healthy, age‐matched controls. A comparison was made between three components from WGE and the DTI metrics FA, MD, PD, and RD, for the detection of differences between patients and controls. It was hypothesized that the stiffness values in the CSTs of the patients would be significantly lower due to the known neurodegeneration associated with ALS. Results Two anisotropic shear moduli polarized parallel and perpendicular to the CSTs were significantly reduced in ALS patients (P < 0.0001), whereas the anisotropic longitudinal modulus polarized parallel to the CSTs showed no significant differences. Conclusion The results of this study suggest a relatively high sensitivity of two anisotropic shear moduli as noninvasive metrics for the assessment of neuronal degeneration within the CSTs. Magn Reson Med 72:1755–1761, 2014. © 2013 Wiley Periodicals, Inc.